Growth Responses of Zoysia spp. under Tree Shade in the Midwestern United States - Peterson, Kenton W.; Fry, Jack D.; Bremer, Dale J. (My University, 2015)
‘Meyer’ zoysiagrass (Zoysia japonica Steudel) is commonly planted on home lawns and golf courses in the transition zone; however, poor shade tolerance limits its widespread use. This study was conducted to determine changes and differences in growth among selected Zoysia cultivars and progeny under a natural shade environment over a 3-year period in the transition zone. The study was initiated in June 2010 at the Rocky Ford Turfgrass Research Center in Manhattan, KS. Soil type was a Chase silt loam (fine, montmorillonitic, mesic, Aquic, Argiudoll). Zoysia genotypes were sodded in 0.37-m2 plots and arranged in a randomized complete block with five replications under silver maple (Acer saccharinum L.) shade that resulted in a 91% reduction in photosynthetically active radiation (PAR). Genotypes included ‘Zorro’ [Z. matrella (L.) Merrill], ‘Emerald’ [Z. japonica × Z. pacifica (Goudswaard) Hotta & Kuroki], ‘Meyer’, Chinese Common (Z. japonica), and experimental progeny Exp1 (Z. matrella × Z. japonica), and Exp2 and Exp3 [(Z. japonica × Z. pacifica) × Z. japonica]. ‘Zorro’ and ‘Emerald’ experienced winter injury, which negatively affected their performance. Tiller numbers decreased 47% in ‘Meyer’ from June 2010 to June 2012, but declines in [(Z. japonica × Z. pacifica) × Z. japonica] progeny were only 1% for Exp2 and 27% for Exp3, and both Exp2 and Exp3 maintained high percent green cover throughout the study. In general, by the third year of evaluation, progeny of [(Z. japonica × Z. pacifica) × Z. japonica] had higher quality ratings and higher tiller numbers than ‘Meyer’ and may provide more shade-tolerant cultivar choices for transition zone turf managers.
Keywords: Zoysiagrass; Zoysia japonica; Zoysia matrella; Zoysia pacifica